Species diversity and polyunsaturated fatty acid content of thraustochytrids from fallen mangrove leaves in Chon Buri province, Thailand - Jaritkhuan, Somtawin; Suanjit, Sudarat (Agriculture and Natural Resources, 2018)
Screening and isolation were carried out of thraustochytrids from fallen, senescent mangrove leaves from three mangrove forests in Chon Buri province, Thailand. In total, 715 thraustochytrid isolates were obtained and classified into 10 species: Aurantiochytrium mangrovei, A. limacinum, Aurantiochytrium sp.1, Aurantiochytrium sp.2, Aurantiochytrium sp.3, Aurantiochytrium sp.4, Aurantiochytrium sp.5, Aurantiochytrium sp.7, Unknown 1 and Unknown 2. The frequency of occurrence of thraustochytrids ranged from 2.50% to 57.50% and was higher in the dry season than the rainy season. The dominant species found in these areas were A. mangrovei and A. limacinum, and the leaves of Avicennia alba had the greatest abundance of A. mangrovei (57.50%) and A. limacinum (28.75%). The biomass of A. mangrovei and A. limacinum was in the range 6.88-22.49 g/L, and 9.39-20.71 g/L, respectively. The highest content of polyunsaturated fatty acids (PUFA) was docosahexaenoic acid (DHA, C22:6n-3) in A. limacinum and A. mangrovei at 1.43-29.67% and 0.84-31.09% of total fatty acid, respectively. The arachidonic acid (ARA, C20:4n-6) and eicosapentaenoic acid (EPA, C20:5n-3) contents were highest in A. limacinum (0.03-0.10% of total fatty acid), and A. mangrovei (0.13-0.60% of total fatty acid), whereas the amount of docosapentaenoic acid (DPA, C22:5n-3) was similar in A. limacinum (0.41-6.08% of total fatty acid) and A. mangrovei (0.23-7.51% of total fatty acid). The results from this study add to the database of biodiversity of thraustochytrids in Thailand and showed that high amounts of C22:6n-3 in some selected strains have potential for use in aquaculture or commercial use.